صوفیۂ برصغیر اور ترکیہ کے ملفوظات کی روشنی میں دعوتِ دین کے مظاہر: تیرہویں صدی عیسوی کے تناظر میں: REFLECTIONS OF PREACHING ISLAM IN MALFŪZĀT OF SUFIS OF SUB-CONTINENT AND TURKEY: A STUDY FROM THE CONTEXT OF 13TH CENTURY: A RESEARCH STUDY - Hafiz Mudassar Farooq; Dr Saeed Ahmad Saeedi (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Malfūzāt Literature of the subcontinent in 13th century contains on discourses of Khāwājā Nizām al Din named “Fawāid al Fawād”, while on the other hand, in turkey the collections of Maulānā jalāl al Din Rumi named “Fihi Ma Fihi” and “Majalis e Saba’a” are prominent. In this research, it is examined that Sufis used to emphasize practical preaching more than verbal preaching. They claimed that the companionship of righteous persons is more important for guidance. They teach the lessons to their followers to adopt the right path and to avoid the evils. According to their teachings, it is clarified that obedience to Holy Prophet is a way to the success in every field of life. They narrate that worship is not only related to the performance of actions but they advise to put forward the same concept of worship which is explained in hadith e Jibrail. From the contents of this article, it is very clear that according to the great Sufis there is unity in Shariah and Tariqah and there is no difference between them.